Investigation on the effect of several parameters involved in the biodegradation of polyethylene (PE) and low-density polyethylene (LDPE) under various seawater environments - Sarra N. Dimassi; John N. Hahladakis; Mohamed Chamkha; Mohammad I. Ahmad; Mohammad A. Al-Ghouti; Sami Sayadi (Science of The Total Environment, 2024)

Effect of temperature and sunlight on the leachability potential of BPA and phthalates from plastic litter under marine conditions - Sarra N. Dimassi; John N. Hahladakis; Mohamed Nejib Daly Yahia; Mohammad I. Ahmad; Sami Sayadi; Mohammad A. Al-Ghouti (Science of The Total Environment, 2023)

Insights into the degradation mechanism of PET and PP under marine conditions using FTIR - Sarra N. Dimassi; John N. Hahladakis; Mohamed Nejib Daly Yahia; Mohammad I. Ahmad; Sami Sayadi; Mohammad A. Al-Ghouti (Journal of Hazardous Materials, 2023)

Pre-assessments of plant conservation status in islands: the case of French Overseas Territories - S. Véron; A. Bernard; E. Lebreton; C. Rodrigues-Vaz; M. Durand; L. Procopio; M. Hélion; M. Gayot; G. Viscardi; G. A. Krupnick; C. M. S. Carrington; V. Boullet; et al. (Biodiversity and Conservation, 2023)

Feasibility of the 4 per 1000 aspirational target for soil carbon: A case study for France - Manuel P. Martin; Bassem Dimassi; Mercedes Román Dobarco; Bertrand Guenet; Dominique Arrouays; Denis A. Angers; Fabrice Blache; Frédéric Huard; Jean‐François Soussana; Sylvain Pellerin (Global Change Biology, 2021)
Increasing soil organic carbon (SOC) stocks is a promising way to mitigate the increase in atmospheric CO 2 concentration. Based on a simple ratio between CO 2 anthropogenic emissions and SOC stocks worldwide, it has been suggested that a 0.4% (4 per 1000) yearly increase in SOC stocks could compensate for current anthropogenic CO 2 emissions. Here, we used a reverse RothC modelling approach to estimate the amount of C inputs to soils required to sustain current SOC stocks and to increase them by 4‰ per year over a period of 30 years. We assessed the feasibility of this aspirational target first by comparing the required C input with net primary productivity (NPP) flowing to the soil, and second by considering the SOC saturation concept. Calculations were performed for mainland France, at a 1 km grid cell resolution. Results showed that a 30%–40% increase in C inputs to soil would be needed to obtain a 4‰ increase per year over a 30‐year period. 88.4% of cropland areas were considered unsaturated in terms of mineral‐associated SOC, but characterized by a below target C balance, that is, less NPP available than required to reach the 4‰ aspirational target. Conversely, 90.4% of unimproved grasslands were characterized by an above target C balance, that is, enough NPP to reach the 4‰ objective, but 59.1% were also saturated. The situation of improved grasslands and forests was more evenly distributed among the four categories (saturated vs. unsaturated and above vs below target C balance). Future data from soil monitoring networks should enable to validate these results. Overall, our results suggest that, for mainland France, priorities should be (1) to increase NPP returns in cropland soils that are unsaturated and have a below target carbon balance and (2) to preserve SOC stocks in other land uses.